Optimalisasi Kolaborasi Mahasiswa KKN 26 dan Masyarakat Desa Munggugianti untuk Menciptakan Program Kerja Lingkungan dan Pendukungnya sehingga Tercapai Tujuan yang Saling Menguntungkan - Indah, Fany; Muhammad Puji Sampurno; Nur Rizqi Syaifullah I; Nurul Aulia Rahma; Reksa Arsilia; Rida Ayu Mustifani Suprayitno (P3M Politeknik Perkapalan Negeri Surabaya, 2024)
The community service program (KKN) is evidence of the role of higher education in community life, especially in rural areas, which is applied as part of the study curriculum. Where students must strive to become part of the community and actively engage in various two-way collaborations that exist in the community environment. This program aims to provide real experience to students in the application of knowledge that has been learned in lectures, as well as provide benefits to the village community and universities so as to create collaboration which is the initial goal. One of the universities that has carried out the role of service to the community is Semen Indonesia International University (UISI) which has carried out KKN “ESON SERU” activities in the even semester of 2024 by carrying out a three-stage planning system and with a “Hybrid System”, which combines activities without staying overnight and overnight activities in the target village, the KKN program focuses on the main focus (Environmental Focus, However, in addition to these three focuses, students are still given the opportunity to contribute directly to the community by helping them with what they need so that a reciprocal relationship will be created and with the main hope that not only the transfer of knowledge given by students to the village, but there is a transfer of value given by the village to students and the campus. One of these KKN locations is in Munggugianti Village, Benjeng District, Gresik Regency. This village is divided into 2 hamlets, namely Munggu and Gianti Hamlets which are led by the Village Head named Fathur Rozi, S.Sos. The implementation of KKN took place from July 15, 2024 to July 25, 2024 by carrying out a work program focused on the environment carried out by Group 26. The main work programs of group 26 are GSOS (Waste Management Awareness Movement), KBAJ (Plastic Replacement Shopping Bags) and POMO (The Importance of Organic Problems). In addition to these three work programs, group 26 is also active in collaborative activities between village officials, PKK group, and other KKN groups that have the same goal, namely to increase public awareness of the importance of protecting the environment by processing organic and inorganic waste and reducing the use of plastic waste. All planned work programs have run smoothly and received good enthusiasm from the surrounding community.